Shoulder and elbow injuries in soccer goalkeepers versus field players in the National Collegiate Athletic Association, 2009-2010 through 2013-2014 - Goodman, A. D.; Etzel, C.; Raducha, J. E.; Owens, B. D. (The Physician and Sportsmedicine, 2018)
Objectives: Examination of the incidence of shoulder and elbow injuries in the collegiate soccer player population is limited, as is comparison between goalkeepers and field players. We hypothesized that goalkeepers would have a higher incidence of shoulder and elbow injuries than field players. Furthermore, we sought to determine the incidence of shoulder and elbow injuries among National Collegiate Athletic Association (NCAA) soccer players, and to determine injury risk factors.